Regional Dimensions of Recent Weakness in Investment : Drivers, Investment Needs and Policy Responses - Vashakmadze, Ekaterine; Kambou, Gerard; Chen, Derek; Nandwa, Boaz; Okawa, Yoki; Vorisek, Dana (World Bank, Washington, DC, 2017)
Investment growth in many emerging market and developing economies (EMDEs) has slowed sharply since 2010. Investment growth performance has varied significantly across different regions, however. This paper examines the temporal evolution of investment growth in six EMDE regions, documents remaining investment needs, especially for infrastructure, and presents a set of region-specific policy responses to address these needs. It reports three main findings. First, investment growth has been particularly weak in EMDE regions with a large number of commodity exporters. In regions with a substantial number of commodity-importing economies, investment growth has been somewhat resilient but has also declined steadily since 2010. Second, sizable investment needs remain in most EMDE regions to make room for expanding economic activity and rapid urbanization. A sizeable portion of these investment needs is in infrastructure and human capital. Finally, while specific policy priorities vary across regions, several policy options to address remaining investment needs apply universally. These include more, or more efficient, public investment and measures to improve overall growth prospects and the business climate. Improved project selection and monitoring, as well as better governance, may enhance the efficiency and benefits from public investment.